Karakteristik Asam Resin Kopal Agathis loranthifolia Sukabumi (Characteristic Resin Acid of Kopal Agathis loranthifolia Sukabumi) - Ika Resmeiliana; Kurnia Sofyan; Suminar S. Achmadi (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2014)
Copal is originated from the exudate of Agathis loranthifolia tree, which flows out from tapping. copal is one of Indonesia's export comodities. Unfortunately, since the export was still in the form of raw materials, it was necessary to study the identification of resin acid content of the copal of Sukabumi. It was also necessary to test the quality of the copal. Extraction was done by using acetone: MeOH (9:1) solvent. Then the extraction of resin acid content was identified by using Gas Chromatography Mass Spectrometry (CGMS). The quality of copal was evaluated based on SNI 7634-2011. Resin acids of the copal which were identified by CGMS are limonene (44%), ethylene oxide hexamer, cis-limonene oxide, toluene, trans-carveol, 2-siclohexane-1-one, trans-limonene oxide, and alpha pinene. Copal of Sukabumi belong to the first class, because the obtained parameters are not all included in the premier class ranges. However it is still possible to be upgraded to their premier class by removing the dirt.Keywords : Agathis loranthifolia, copal, limonene, resin acids.